2005
DOI: 10.1007/s11144-005-0298-y
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of catalytic activity of titanosilicalite-1 - sulfated zirconia combination towards epoxidation of 1-octene with aqueous hydrogen peroxide

Abstract: Titanosilicalite-1 (TS-1) in combination with sulfated zirconia efficiently catalyzes the epoxidation of 1-octene with aqueous hydrogen peroxide. The presence of both octahedral zirconium and sulfate species in the catalysts enhances the epoxidation rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
(7 reference statements)
1
10
0
1
Order By: Relevance
“…Meanwhile, the higher activity observed in the sample with lower V 2 O 5 loading indicated that only small amount of V 2 O 5 is needed to increase the hydrophilicity of TS-1 to form peroxotitanium species. Similar findings have been reported by Prasetyoko et al [11], which reported that the yield of 1,2-epoxyoctane from 1-octene epoxidation decreased as WO 3 loading in TS-1 increased higher that 7 wt% due to the blocking pores of TS-1 by tungsten oxide WO 3 at the high amount of WO 3 loading in TS-1.…”
Section: B Catalytic Activitysupporting
confidence: 90%
See 1 more Smart Citation
“…Meanwhile, the higher activity observed in the sample with lower V 2 O 5 loading indicated that only small amount of V 2 O 5 is needed to increase the hydrophilicity of TS-1 to form peroxotitanium species. Similar findings have been reported by Prasetyoko et al [11], which reported that the yield of 1,2-epoxyoctane from 1-octene epoxidation decreased as WO 3 loading in TS-1 increased higher that 7 wt% due to the blocking pores of TS-1 by tungsten oxide WO 3 at the high amount of WO 3 loading in TS-1.…”
Section: B Catalytic Activitysupporting
confidence: 90%
“…Hydrophilic improvement of catalyst can be carried out by addition of metal oxide which leads to increasing of acidity properties. The metal oxide in TS-1 catalyst which act as acid site capable to increase catalyst hydrophilicity, so that reactant adsorption in catalyst becomes faster [10,11]. In previous research done by Indrayani [12], MoO 3 /TS-1 catalysts have showed improvement of hydrophilicity along with the increasing of MoO 3 content in MoO 3 /TS-1 catalyst.…”
mentioning
confidence: 99%
“…Isolated metal centers and small oligomers of early transition metal oxides (e.g., Al III [14,15], Ti IV [7,[16][17][18], Zr IV [19,20], Ta V [21][22][23], and Nb V [24,25]) catalyze the epoxidation of olefins with H 2 O 2 . Isolated Nb atoms grafted onto silica give greater rates and selectivities for olefin epoxidation compared to isolated Ti centers as well those of other group IV and V metals (i.e., Zr, Hf, V, and Ta) on silica, which was attributed to differences between the Lewis acidity (estimated from the ionic character of the M-O bond) of the different metal atoms [20].…”
Section: Introductionmentioning
confidence: 99%
“…Zr and Hf organometallic complexes have been used for alkene epoxidation using tert-butyl hydroperoxide as the oxidant. 52 Our work facilitates the catalytic transfer of both oxygen atoms from molecular O 2 to substrate molecules (e.g., alkene) to produce substrate oxide molecules (e.g., alkene oxide) without requiring a coreductant. 49 A Zr organometallic complex activated molecular oxygen that subsequently epoxidized an olen group in a non-catalytic reaction in which the formed epoxide remained covalently bound to the metal and a methyl group on one of the ligands was irreversibly reduced to a methoxy group.…”
Section: Introductionmentioning
confidence: 99%